2016
DOI: 10.5505/turkhijyen.2016.57805
|View full text |Cite
|
Sign up to set email alerts
|

Environmental risk assessment under the pollutants exposure with using four lichen species and molecular assay in cement plant, Aşkale-Erzurum (Turkey)

Abstract: ÖZET Amaç:Aşkale Following the exposure to the pollutants of 1, 2 and 3 district situated at a distance of 50, 100, 200m to the cement factory, P. furfuracea with a control bands were observed respectively. Moreover 31, 13 and 15 bands from the control species disappeared in sites 1, 2 and 3 in P. furfuracea samples. Furthermore, the highest polymorphism value was obtained (P% = 86,6%) in U. longissima and L. pulmonaria by the OPC04 primer, and the lowest polymorphism was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Environmental stressors such as heavy metal pollution can induce mutations and toxic effects, leading to the disruption of DNA integrity [40]. Therefore, the determination of DNA damage in terrestrial organisms living in polluted areas is a considerable exponent in ecotoxicology studies [6,41]. As a result of the comparing of band differences of RAPD and Coupled Restriction Enzyme Digestion-Random Amplification (CRED-RA) analysis, it was determined that the rate of change in the methylation model of the samples exposed to heavy metal stress varies more than the samples exposed to UV radiation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Environmental stressors such as heavy metal pollution can induce mutations and toxic effects, leading to the disruption of DNA integrity [40]. Therefore, the determination of DNA damage in terrestrial organisms living in polluted areas is a considerable exponent in ecotoxicology studies [6,41]. As a result of the comparing of band differences of RAPD and Coupled Restriction Enzyme Digestion-Random Amplification (CRED-RA) analysis, it was determined that the rate of change in the methylation model of the samples exposed to heavy metal stress varies more than the samples exposed to UV radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been published to determine the genotoxicity with DNA molecular markers of heavy metals exposure in lichens. Hamutoğlu et al [6] observed that there were 19, 45 and 51 bands in P. furfuracea (control band number 83), respectively, after the 1st, 2nd and 3rd regions, located 50, 100 and 200m away from the cement factory that was exposed to contaminants. Sorrentino et al [42] investigated with ISSR molecular markers in moss Sphagnum palustre for showing both Cd and Pb salts a genotoxic effect in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lobaria pulmonaria has been employed as a monitoring tool (as a biomonitor and/or as a bioindicator) in studies carried out in forest habitats around specific pollution sources [50][51][52][53][54]117,118]; in remote forest sites [55][56][57]; and in sites concerned by the long-range transportation of pollutants, such as radionuclides [77][78][79][80][81][82], acid rain depositions [119,120], or under controlled conditions in relation to specific pollutants [58][59][60][61][62][63].…”
Section: Monitoring With Lobaria Pulmonariamentioning
confidence: 99%